The use of the tic ́s key trigger of the teaching/learning process - Pérez Pérez, Isabel; Orozco Gutiérrez, Mario; Hidalgo González, Ramiro A. (Universidad Francisco de Paula Santander, 2016)
This study analyzes the use of ICTs in primary schools in Tonalá, Chiapas as a key trigger in learning for basic level students. For this purpose, a semi-structured survey was prepared that allowed data to be obtained from a sample of 187 students, where 51.34% are girls and 48.66% are boys, the average age is 56.68% of 11 years, 26.74% of 12 years, 11.23% of 13 years and the remaining 5.35% of 10 years. Concluding that there are both pedagogical, didactic, strategic and organizationallimitations in the teaching-learning processes, due to the lack of infrastructure, followed by the pedagogical and didactic shortcomings of the teacher who imparts the subject of new technologies and does not dominate this technological tool, reducing the active knowledge in the students, negatively influencing their attitude and the quality of the new 2016 educational model. But if the skills necessary for daily life related to the exploration, classification and reflexive analysis of the data are significantly improved. Web 2.0 Optimizing oral expression skills and student awareness regarding the use of the computer in sustainable development in primary education